Physicochemical, thermal, and polymorphic properties of binary blends from bambangan stearin and palm stearin - Norazlina Mohammad Ridhwan; Hasmadi Mamat; MD JAHURUL HAQUE AKANDA; MACDALYNA ESTER RONIE; AHMAD HAZIM ABDUL AZIZ (UNIMAS, 2025)
Increasing demand for sustainable and functional fat alternatives in the food industry has prompted research into fat modification resulting in specialty fats production that can imitate cocoa butter. This study investigates the binary blends of bambangan and palm stearin, focusing on their physicochemical, thermal, and morphological properties. The blends were blended in five different ratios, with the addition of palm stearin not exceeding 30%. The results show that the iodine value (33.78 to 34.24 g iodine+/g), slip melting point (33.25 to 38.35 °C), and acid value (1.31 to 1.59 mgKOH/g) of the blends were influenced by the palm stearin content. The melting behaviour and crystallisation properties of the blends analysed using differential scanning calorimetry revealed an improved melting profile compared to the palm stearin. The binary blends exhibited desirable polymorphic transitions to the stable β(v) form, preferred for chocolate applications. Notably, the blend with 70% bambangan stearin and 30% palm stearin (BS5) demonstrated an improved triglyceride profile with a reduction of tripalmitin content and melting properties similar to cocoa butter, reducing the waxy texture typically associated with palm stearin. The findings suggest that BS5 produced from bambangan seed waste is a functional, cost-effective alternative confectionery product, offering stability and desirable thermal properties.